2021
DOI: 10.1007/s12975-021-00891-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-Based Outcome Prediction of Acute Intracerebral Hemorrhage

Abstract: We hypothesized that imaging-only-based machine learning algorithms can analyze non-enhanced CT scans of patients with acute intracerebral hemorrhage (ICH). This retrospective multicenter cohort study analyzed 520 non-enhanced CT scans and clinical data of patients with acute spontaneous ICH. Clinical outcome at hospital discharge was dichotomized into good outcome and poor outcome using different modified Rankin Scale (mRS) cut-off values. Predictive performance of a random forest machine learning approach ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…The CNN has an overfitting problem that affects the performance of the prediction method. Nawabi et al [ 55 ] applied random forest with filter and texture-derived features for the prediction process. The developed method with the selected features achieved higher performance in the analysis.…”
Section: Review Of Sah Prediction Modelsmentioning
confidence: 99%
“…The CNN has an overfitting problem that affects the performance of the prediction method. Nawabi et al [ 55 ] applied random forest with filter and texture-derived features for the prediction process. The developed method with the selected features achieved higher performance in the analysis.…”
Section: Review Of Sah Prediction Modelsmentioning
confidence: 99%
“…The same algorithm also identified subtle ICHs that were overlooked by radiologists further underlining the potential of machine-learning aided decision making in ICH diagnosis, especially in times of increasing imaging workloads [72]. Another group found that machine learning-based evaluation of image features provided the same discriminatory power in predicting functional outcome as multidimensional clinical scoring systems and that the integration of conventional scores and image features had synergistic effects with an increase of accuracy for prediction functional outcome in patients with ICH [73]. Further, mobile stroke units may not only help in the early diagnosis of ischemic stroke but also add to rapid diagnosis of ICH and to correctly triaging these patients to the appropriate hospital, which may especially be important in rural areas [74][75][76].…”
Section: Future Perspectivesmentioning
confidence: 91%
“…In patients with intracerebral hemorrhage (ICH), the ICHscore is one of the most widely used clinical prediction scores (85)(86)(87)(88). Although ML technology for outcome prediction has rapidly advanced for ischemic stroke, recent ML studies predicting functional outcomes after ICH have also demonstrated high-discriminating power (63,89). A recent study by Sennfält et al tracked long-term functional dependence and mortality after an acute ischemic stroke of more than 20,000 Swedish patients (90).…”
Section: Machine Learning In Stroke Outcome Predictionmentioning
confidence: 99%